Electrode Distances Of Microbial Fuel Cell System On Salted Boiled Fish Processing Wastewater To Electricity And Pollution Load - Bustami Ibrahim; Pipih Suptijah; Bagus Sukma Agung (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Microbial fuel cell (MFC) is a technology produce electricity by helping exoelectrogenic bacteria. Thetechnology can also utilize fishery processing wastewater as a media for bacteria to live, so it reduces organicpollution load in the wastewater. The purpose of this research was to identify the effect of electrodes distanceto electricity and water quality parameters of fisheries processing wastewater using MFC technology.. TheMFC system used was single chamber system. The distance between electrodes applied were 2 cm, 4 cmand 6 cm and the electrodes were made of stainless wire mesh coated with chitosan and active carbon.The results showed that electrodes distance affected to MFC electricity within salted boiled fish wastewatermedia. The average value of electric current during 48 hours observation on the distance of 2 cm, 4 cm and6 cm were 0.17±0.06 mA, 0.46±0.17 mA and 0.44±0.16 mA, respectively. Average values of electric voltageon the distance of 2 cm, 4 cm and 6 cm were 0.12±0.03 V, 0.34±0.07 V and 0.37±0.08 V, respectively. Theresearch also showed that MFC system can decrease average value of BOD 20.5%, COD 30.41%, and TAN21.2 % of salted boiled fish wastewater media.